Religious, ethical and psychological aspects of overzealous treatment.A qualitative research in the group of Japanese Roman Catholics - Olejarz, Sylwia Maria (Current Problems of Psychiatry, 2012)
This article examines doubts and concerns regarding overzealous treatment in the group of Japanese Roman Catholics.